Meta analysis of the effect of STEM application on higher order thinking skill in science learning - Azizahwati Azizahwati; Januarti Januarti; Siti Wulan Sari; Ranti Amelia Sari; Linda Ranti; Rury Septyowaty (Momentum: Physics Education Journal, 2023)
The purpose of this research is to ascertain the impact of using the STEM approach in learning science and physics. The 20 research articles whose findings were examined in this study were all published in journals between 2018 and 2022. Effect size values used in the meta-analysis in this study were calculated using the OpenMEE program. Four indicators—level of education, learning models, learning media, and higher-order thinking skills—can be used to determine the impact of STEM (HOTS) learning. The average effect size on educational attainment is 1,590 at the junior high school level and 1,440 at the senior high school level. The average effect size for STEM learning with the PjBL learning model is 1.490, PBL is 1.250 and inquiry learning is 0.333. According to the average effect size results obtained for LKPD of 1.878, module of 1.818, and LKP of 1.503, this study examines the impact of STEM on the media. The average effect size score was obtained for higher order thinking skills (HOTS) for problem solving skills of 1.699, critical thinking skills of 1.899, scientific literacy abilities of 1.126, concept understanding of 0.997, and creative thinking abilities of 0.951. According to the findings of the effect size study, STEM learning is appropriate for use at the junior high school level with the PjBL learning approach using LKPD learning media to strengthen students' critical thinking skills.